2020
DOI: 10.1021/acs.jpclett.0c02809
|View full text |Cite
|
Sign up to set email alerts
|

Long-lasting Salt Bridges Provide the Anchoring Mechanism of Oncogenic Kirsten Rat Sarcoma Proteins at Cell Membranes

Abstract: RAS proteins work as GDP-GTP binary switches and regulate cytoplasmic signalling networks that are able to control several cellular processes, playing an essential role in signal transduction pathways involved in cell growth, differentiation and survival so that overacting RAS signalling can lead to cancer. One of the hardest challenges to face is the design of mutation-selective therapeutic strategies. In this work, a G12D mutated farnesylated GTP bound Kirsten RAt Sarcoma (KRAS) protein has been simulated at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(55 citation statements)
references
References 60 publications
(99 reference statements)
9
44
0
Order By: Relevance
“…S7 and S8 of Ref. 19 ) which help to stabilize KRas-4B-Far binding with the interface of the membrane, regardless of its farnesyl group anchoring into the membrane or not. In the present case, we have observed that under the circumstances of phosphorylation at Ser-181, the O f me of farnesyl group forms typical HB with the phenoxyl hydrogen atom belonging to Tyr137 of CD (see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…S7 and S8 of Ref. 19 ) which help to stabilize KRas-4B-Far binding with the interface of the membrane, regardless of its farnesyl group anchoring into the membrane or not. In the present case, we have observed that under the circumstances of phosphorylation at Ser-181, the O f me of farnesyl group forms typical HB with the phenoxyl hydrogen atom belonging to Tyr137 of CD (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since oncogenic Ras is defective in GAP-mediated GTP hydrolysis it results in an ac-residues 1-166, in a sequence which contains a catalytic lobe (the effector-binding domain, residues 1-86) and an allosteric lobe (residues . HVR preferentially binds the membrane in the liquid crystal phase, by inserting its farnesyl moiety into the phospholipid bilayer 18,19 . Ras proteins are distinguished by their unique HVR post-translational modifications (PTM).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations